Determination of bisphenol A‐glucuronide in human urine using ultrahigh‐pressure liquid chromatography/tandem mass spectrometry. (10th January 2016) - Hauck, Zane Z.; Huang, Ke; Li, Guannan; van Breemen, Richard B.
Abstract : Rationale: Used widely as a plasticizer and as a monomer for plastics, bisphenol A (BPA) is under investigation as a possible endocrine disrupter. As an indication of systemic exposure, a fast and accurate assay was developed for the major BPA metabolite in human urine, BPA‐monoglucuronide (BPA‐G), using ultrahigh‐pressure liquid chromatography/tandem mass spectrometry (UHPLC/MS/MS). Methods: Urine samples were prepared using solid‐phase mixed‐mode reversed‐phase/anion‐exchange extraction. BPA‐G was measured using UHPLC/MS/MS with an amide UHPLC column interfaced to a triple‐quadrupole mass spectrometer equipped with negative ion electrospray, collision‐induced dissociation and selected reaction monitoring. [ 13 C12 ]‐BPA‐G was used as a surrogate standard. Results: By measuring the glucuronide metabolite of BPA, potential interference due to BPA contamination from containers, solvents, pipette, etc., was avoided. The standard curve had a linear regression coefficient of 0.999, and the intra‐ and inter‐assay variations were less than 10%. The assay was validated according to FDA guidelines. Conclusions: A fast, accurate, and highly selective method for the determination of BPA‐G in human urine was developed and validated using UHPLC/MS/MS. This method is suitable for assessing human exposure to BPA. Copyright © 2016 John Wiley & Sons, Ltd.